PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN TERHADAP KINERJA MANAJERIAL: TINJAUAN LITERATUR SISTEMATIS - Nadhea Salsabila; Riri Novita; Suci Wulandari; Anjely Larasati (STKIP Subang, 2026)
This study aims to analyze the implementation of responsibility accounting on managerial performance using a systematic literature review approach. The research method used is Systematic Literature Review (SLR) with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. Data were collected from scientific databases such as Google Scholar and Garuda with a publication range from 2015–2024. The article selection process involved identification, screening, eligibility, and inclusion stages. The initial search identified 135 articles, and after the selection process, 20 relevant articles were included in the final analysis. The results indicate that the implementation of responsibility accounting positively affects managerial performance by improving cost control effectiveness, managerial accountability, and decision-making processes. This study contributes to the development of management accounting literature and provides references for organizations in improving management control systems.